2023
DOI: 10.1007/s00253-023-12563-8
|View full text |Cite
|
Sign up to set email alerts
|

Linocin M18 protein from the insect pathogenic bacterium Brevibacillus laterosporus isolates

Abstract: Brevibacillus laterosporus (Bl) is a Gram-positive and spore-forming bacterium. Insect pathogenic strains have been characterised in New Zealand, and two isolates, Bl 1821L and Bl 1951, are under development for use in biopesticides. However, growth in culture is sometimes disrupted, affecting mass production. Based on previous work, it was hypothesised that Tectiviridae phages might be implicated. While investigating the cause of the disrupted growth, electron micrographs of crude lysates showed structural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…The C33 strain has a gene encoding the Linocin M18 bacteriocin; a protein that forms nano compartments within the pathogenic bacterium, it also contains ferritin-like proteins or peroxidases and enzymes involved in the oxidative stress response. Various authors have reported that Linocin M18 has bacteriostatic activity against strains of Arthrobacter, Bacillus, Brevibacterium, Corynebacterium, and Listeria [58]. In addition, C33 presents with genes encoding Zoocin A, a peptidoglycan hydrolase, which, combined with lauricidin, a cell membrane active lipid, has been reported to selectively suppress the growth of Streptococcus mutans [59].…”
Section: Discussionmentioning
confidence: 99%
“…The C33 strain has a gene encoding the Linocin M18 bacteriocin; a protein that forms nano compartments within the pathogenic bacterium, it also contains ferritin-like proteins or peroxidases and enzymes involved in the oxidative stress response. Various authors have reported that Linocin M18 has bacteriostatic activity against strains of Arthrobacter, Bacillus, Brevibacterium, Corynebacterium, and Listeria [58]. In addition, C33 presents with genes encoding Zoocin A, a peptidoglycan hydrolase, which, combined with lauricidin, a cell membrane active lipid, has been reported to selectively suppress the growth of Streptococcus mutans [59].…”
Section: Discussionmentioning
confidence: 99%